ANALISIS KONDISI PEMBELAJARAN BAHASA MANDARIN PADA SEKOLAH TAMAN KANAK-KANAK BILINGUAL DI PONTIANAK (Studi Kasus pada Taman Kanak-Kanak Kinderfield dan Taman Kanak-Kanak Adicita Mulia) - Salsabila, Salsabila; Ina, Ina; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
To understand the process of learning Mandarin in Pontianak Bilingual Kindergarten, the author took Kinderfield Kindergarten and Adicita Mulia Kindergarten as research objects. The research methods used were purpose sampling, interviews and observations. The author will analyze relevant learning materials, learning objectives, learning evaluation, learning environment and learning methods to determine the situation of learning Mandarin in kindergartens in Pontianak. According to the results of data analysis, Mandarin classes are only given once a week at school. Because there is less time to learn Mandarin, the teacher only introduces everyday vocabulary, the aim is for students to understand the meaning of everyday Mandarin vocabulary. Teachers use translation methods, game methods, and object methods to explain vocabulary. Pontianak Bilingual Kindergarten uses various teaching methods to make the class more active, such as using children's songs, playing games together, etc. so that it can increase children's interest in learning and not put too much pressure on children. Students read the vocabulary words one by one and the teacher will evaluate their learning, to see if students have made progress in Mandarin and what help they still need.